Competition Study of Cowpea (Vigna unguiculata L. Walp) and Bidens pilosa L. Using Replacement Series Approach - Bachri, Saiful; Subakti, Harun Dwi; Putri, Salsabila Adya Maharani; Tjirosemito, Soekisman (SEAMEO BIOTROP, 2023)
Weeds disturb plants through competition or competition that occurs with cultivated plants. Weed competition can reduce crop production by up to 40%, as well as reduce seed quality. The amount of competition between weeds and plants is determined by the density of weeds, the length of time they grow with cultivated plants, and the type of weeds. Thus, it is necessary to increase productivity by considering the presence of weeds that can reduce production. On this basis, it is necessary to conduct research on the competition between cowpea and weeds using the replacement series method. Replacement series is a method used to evaluate competition between species by studying interspecific and intraspecific interactions of plant combinations. This research was carried out in the greenhouse of SEAMEO BIOTROP July – September 2021. This study used a simple randomized block design with a single factor, namely the composition of weeds with 5 treatment levels, namely: P1: 100% weeds. , P2: 75% weeds + 25% cowpeas, P3: 50% weeds + 50% cowpeas, P4: 25% weeds + 75% cowpeas, and P5: 100% cowpeas. The observation parameters are growth parameters represented by plant height variables and yield parameters are represented by dry weight. The results showed that the increasing proportion of weeds was accompanied by a decrease in the dry weight of cowpea. Vice versa. Then, the results of plant height measurements show that the increasing proportion of weeds and plants will be accompanied by a decrease in the height of their competitors. The results of the analysis of RYT values showed that there was competition between weeds and cowpeas at the P3 treatment level: 50% weeds and 50% cowpeas. Meanwhile, in other proportions there is a negative interaction.